Ischemic Priapism in a 12 Year Old Patient Associated With Coronavirus Disease 2019 (COVID-19): A Case Report - Brönimann, Stephan; Thalhammer, Florian; Springer, Alexander; Tonnhofer, Ursula; Shariat, Shahrokh F; D'Andrea, David (Urology, 2022)
Infection with Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) has been associated with changes in blood coagulation resulting in increased incidence of venous thromboembolic events and coagulopathy. Moreover, single cases of ischemic priapism have been reported in adult patients with SARS-CoV-2 infection. In this report, we describe the case of ischemic priapism in a 12-year-old child with recent SARS- CoV-2 infection.
Keywords: žilní tromboembolie; Venous Thromboembolism; Humans; Venous Thrombosis; Child; lidé; mužské pohlaví; SARS-CoV-2; Male; dítě; Priapism; žilní trombóza; COVID-19; priapismus